Sorafenib and pegylated interferon-α2b in advanced metastatic melanoma: a multicenter phase II DeCOG trial - Egberts, Friederike; Gutzmer, R.; Ugurel, S.; Becker, J. C.; Trefzer, U.; Degen, A.; Schenck, F.; Frey, L.; Wilhelm, T.; Hassel, Jessica C.; Schadendorf, D.; Livingstone, E.; et al. (Annals of oncology, 2011)
Background - The combination of sorafenib, a multikinase inhibitor, and pegylated interferon-α2b (Peg-IFN-α2b) could potentially lead to an improved antitumoral response. Previously, combinations of interferon and sorafenib have been used in renal cell cancer. - Patients and methods - Patients with stage IV metastatic melanoma and no previous systemic therapies apart from adjuvant immunotherapy received Peg-IFN-α2b 3 μg/kg once per week, and sorafenib 400-mg b.i.d. for a minimum of 8 weeks. The primary study end point was disease control rate (DCR). - Results - Between February 2008 and February 2009, 55 patients were enrolled with a median age of 64 years (20-85). At 8 weeks, 2 patients (3.6%) had a partial response (PR) and 14 patients a stable disease (25.5%), for a DCR of 29.1% in the intention-to-treat (ITT) population. The median progression-free survival in the ITT population was 2.47 months (95% confidence interval 1.22-3.72 months). The toxicity of sorafenib and Peg-IFN-α2b combination was characterized by mainly hematological side-effects, including one treatment-related bleeding complication with a fatal outcome. Other grade 3/4 toxic effects were fatigue and flu-like symptoms. - Conclusion - The combination of sorafenib and Peg-IFN-α2b showed modest clinical activity and some serious side-effects including fatal bleeding complications.